Regeneration of aged DMF for use in solid‐phase peptide synthesis. (25th December 2018) - Magtaan, Jordan Kevin; Devocelle, Marc; Kelleher, Fintan
Abstract : Dimethylformamide (DMF), which is still the most commonly used solvent for Fmoc‐SPPS, has the potential for degradation over time on exposure to air (and water vapour) and storage, to give dimethylamine and formic acid impurities. In particular, dimethylamine can lead to unwanted deprotection of the fluorenylmethyloxycarbonyl (Fmoc) group during, for example, the initial loading of Fmoc amino acids in SPPS, which leads reduced calculated loading values. We have found that treatment of such aged DMF by simple sparging with an inert gas (N2 ), or vacuum sonication, can regenerate the DMF in order to restore loading levels back to those found for newer, fresh, DMF samples. Abstract : Treatment of aged dimethylformamide (DMF) containing dimethylamine as an impurity can be simply regenerated, to give resin loading levels in solid‐phase peptide synthesis (SPPS), comparable with newer DMF samples.